2018
DOI: 10.1097/id.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Re-osseointegration of Dental Implants After Periimplantitis Treatments

Abstract: Promising results were observed in the studies that used combination of bone substitutes together with guided bone regeneration for the regenerative therapy. Regarding implant surfaces, better re-osseointegration was observed with rough implant surfaces rather than smooth ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 28 publications
2
38
0
10
Order By: Relevance
“…It was concluded that better results were obtained at rough surfaces compared to turned surfaces and when regenerative therapy was added to the mechanical debridement. However, similar to the present study, re‐osseointegration was also obtained when no regenerative techniques were applied …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It was concluded that better results were obtained at rough surfaces compared to turned surfaces and when regenerative therapy was added to the mechanical debridement. However, similar to the present study, re‐osseointegration was also obtained when no regenerative techniques were applied …”
Section: Discussionsupporting
confidence: 89%
“…The results obtained in the present experiment regarding the gain in coronal bone level are in agreement with the outcomes from other experimental studies on peri‐implantitis treatment. In a recent systematic review on experimental studies on peri‐implantitis treatments, data on re‐osseointegration from 15 studies were analyzed. It was concluded that better results were obtained at rough surfaces compared to turned surfaces and when regenerative therapy was added to the mechanical debridement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the goal is re‐osseointegration, the disinfected implants will be submerged, and the bone defects will be augmented. In these cases, preserving the rough surface is needed, therefore, applying an instrument with the least potential for smoothing the surface becomes favorable …”
Section: Discussionmentioning
confidence: 67%
“…In these cases, preserving the rough surface is needed, therefore, applying an instrument with the least potential for smoothing the surface becomes favorable. 93,94 Qualitative evaluation is a conventional method for measuring the changes in surface morphology. Most of the included studies in this review used SEM to describe surface morphology.…”
Section: Implantitis Irreversible Vertical Bone Loss Occurs Which Rementioning
confidence: 99%